Rural Livelihoods, Resources and Coping with Crisis in Indonesia (ICAS Publications Series / Edited Volumes, 2009)
Most literature on the economic crisis in indonesia has focused on the negative macro-economic impacts during the "crisis- years" of 1997-99. The case studies presented in this book take a different perspective. With a longitudinal research perspective, this comparative study analyses a wide variety of responses to the crisis among communities and households. The case studies in this book cover the coping and adapting mechanisms of rural households under a variety of resource use practices and resource use regulations in different areas of Indonesia. De meeste literatuur over de economische crisis in Indonesië richt zich vooral op de negatieve macro-economische effecten tijdens de hoogtijdagen van de crisis (1997-1999). De case-studies in dit boek beslaan niet alleen een langere periode, er worden ook diepteanalyses gemaakt van een verscheidenheid aan reponse- en bestaansstrategieën van huishoudens en rurale gemeenschappen tijdens en na de crisis. Pessimistische aannames ten aanzien van de weinig effectieve vooronderstellingen worden in dit boek tegengesproken. Het boek levert daardoor een bijdrage aan een effectiever beleid om gemeenschappen in crisissituaties weerbaarder te maken.